STATUS SOSIAL-EKONOMI DAN KEPUASAN PENGHUNI APARTEMEN TRANSIT RANCAEKEK (ATR) SEBAGAI ALTERNATIF HUNIAN MASYARAKAT BERPENGHASILAN RENDAH DI KAWASAN PERI-URBAN METROPOLITAN BANDUNG RAYA - Anita Vitriana (Diponegoro University, 2019)
The research on the relationship between socio-economic status and the residential satisfaction is conducted at Rancaekek Transit Apartment (RTA) that located in Peri-urban Area of Bandung Metropolitan Area. RTA is the largest modest flat that is managed by West Java Provincial Government as alternative dwellings for low-income industrial workers in West Java. As one of the evaluation models of modest flats implementation, this study aims to find out some socio-economic factors which affect the level of satisfaction of the occupants. In this study, the assessment of residential satisfaction was using indicators on physical condition and management of modest flats. The examined socio-economic factors in this research consist of 16 attributes. Data was collected through questionnaires distribution, which spread to 93 respondents of RTA residents. Data processing and analysis of the relationship between satisfaction and socio-economic status were using chi-square bivariate method. The results showed that in the RTA occupancy with residential segments from a homogeneous economic status (low-income industrial workers), there were only social attributes which considered to have significant effects on occupant satisfaction. The four social attributes which have contributed to the level of residential satisfaction consist of the variable of marital status, the number of occupants in one unit, the counterpart of one residential unit and the location of the block.